2014
DOI: 10.1159/000368366
|View full text |Cite
|
Sign up to set email alerts
|

Training in and Experience with Endobronchial Ultrasound

Abstract: Background: Diagnosing mediastinal and hilar lymphadenopathy and staging lung cancer with endobronchial ultrasound (EBUS)-guided transbronchial needle aspiration (TBNA) are on the rise, but uncertainty surrounds the optimal number of cases needed to achieve acceptable yields. Objectives: To determine the threshold at which EBUS-TBNA reaches adequate yields among trainees and skilled bronchoscopists. Methods: We reviewed all EBUS-TBNAs performed at our medical center since implementing the use of EBUS (n = 222)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The importance of the learning curve in the implementation of endoscopic ultrasound application and parallel improvement of diagnostic yield have been clearly demonstrated [21]. pime pime pime pime p pi im me e EDITRICE …”
Section: Discussionmentioning
confidence: 99%
“…The importance of the learning curve in the implementation of endoscopic ultrasound application and parallel improvement of diagnostic yield have been clearly demonstrated [21]. pime pime pime pime p pi im me e EDITRICE …”
Section: Discussionmentioning
confidence: 99%
“…Fifteen studies have described the learning curves for 43 operators performing EBUS (Table ) . Ten studies provided the number needed to gain proficiency based on the cumulative sensitivity over a period . Most of the studies were retrospective and were single centre.…”
Section: Resultsmentioning
confidence: 99%
“…Hu et al [16] reported that the minimum operation cases needed to reach 90% ACC was 22. Bellinger et al [33] reported that a minimum of 20-25 procedures is needed to achieve acceptable yields. Our study showed similar results achieved by the ST and T groups.…”
Section: Discussionmentioning
confidence: 99%